(untitled) (Journal of the College of Education for Women, 2023)
This study aimed to developing the skills of critical reading for the tenth basic school female students through a training program using the reflective thinking method. The study sample consisted of (64) students. To achieve the objective of the study, the researcher uses the quasi-experiment approach consisting of a control group (32 students) and an experimental group (32 students). The researcher used three research inventories as follows: 1) A list of critical reading skills included (30) skills within three aspects (Recognition – Deduction – Evaluation and Judgment). 2) An executive program using reflective thinking for developing critical reading skills. 3) Achievement test to measure critical reading skills. The study reached the following conclusions: 1) A list of critical reading skills required for students hereof included (30) skills within three aspects. 2) Remarkable growth of the student’s critical reading skills according to the effect size results after using the proposed program using the reflective thinking method. 3) There are no significant differences between the average scores of both groups in the post and prior tests attributed to the way of teaching. The study provided various recommendations to develop the field of education.